OPERATIONAL FIELD TESTING BAHAN PEMBELAJARAN GENERASI BARU (Studi pada Matakuliah Geografi dan Pelestarian Lingkungan dalam PIPS Universitas Terbuka) - Sri Sumiyati (ITB AAS INDONESIA Surakarta, 2022)
This study aims to carry out Step Operational Field Testing of New Generation Learning Materials at the Universitas Terbuka (UT) in the Geography and Environmental Preservation Course in PIPS. This research was carried out in Conventional, Blended and Fully Online formats referring to steps 12 – 15 of the R & D model developed by Borg, Walter R. and Gall, Meredith D. (1983) for the macro scale, and the R & D model. according to Borg and Gall (2007) for the micro scale. The results of Step 12 Operational Product Revision are editorial improvements, completing pictures, completing study instructions, improving layouts, improving covers and references. The results of Step 13 Operational Field Testing are that the substance does not change, the addition of sources of learning materials in the form of videos and improvements to the appearance of color forms and illustrations from the cover. The result of Step 14 Final Product Revision is on the research activity of New Generation Learning Materials which is focused on printed/conventional materials as the final product. The result of Step 15 Dissemination and Implementation is that dissemination (without implementation) through national or regional seminars with at least 50 participants and stakeholders has not been carried out because they are waiting for leadership policies.